SIMILES AND AMBIGUOUS MEANING IN HEATHER’S SONG LYRICS – CONAN GRAY - A, A. Reskiyani Ma'sum; Nur, Sahril; Abdullah, Ahmad Rizal (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
This study examines the types of similes in the lyrics of "Heather" using Fromilhague's theory (1995) and the meaning in the lyrics of "Heather" using Hurford and Heasley's theory (2004). This study aims to find the kinds of similes contained in "Heather" and also describe them to the readers in order to get a clearer insight more deeply. Miles, Huberman, and Saldana's data analysis model was used by the researchers (2014). Researchers discovered two data from the lyrics of Conan Gray's song - Heather that are included in implicit similes and two data that are included in explicit similes. The researchers also found that the words used in "Heather" mean very multi-interpretive because it is intentionally vague and biased, allowing it to be interpreted into any meaning, aka ambiguous. Furthermore, researchers discovered 14 data points with structural ambiguity and 15 data points with lexical ambiguity in the song lyrics.